Cultivating Critical and Creative Thinking Skills through an Integrated Approach to the Teaching of Literary Texts - Dhanapal, Saroja (2008)
This research addressed the issue of critical and creative thinking skills (henceforth abbreviated to CCTS) in relation to Malaysian secondary school students. The aim of the study was to establish the current status of CCTS among Malaysian students and to prove the hypothesis that an integrated approach to literary text will enhance the level of CCTS among students. The integrated approach here refers to an approach which combines the reader response approach and stylistics analysis to the teaching of literary texts. The researcher adopted the combination of Benjamin Bloom’s and Cogaff Taxonomy (a taxonomy derived by Dr Ghazali Mustapha) which is labeled as the CCT Taxonomy as a base for the study. The study adopted a quantitative and qualitative research method whereby it incorporates an experiment conducted by way of a pre-test and post-test, an interview of teachers and classroom observation. The data for this study was collected through a survey conducted in two Malaysian secondary schools, one in a rural area and the other in an urban area. The respondents consisted of Form 4 students. In furtherance of the research, an analysis was done on the current methods adopted by the teachers in the schools with the purpose of investigating how far these methods were effective in cultivating CCTS among Malaysian students. The researcher also conducted some classes using the integrated approach to seek evidence that the method advocated (an integrated approach) is more effective for cultivating CCTS among students. The research findings showed that an integrated method is more effective for the purpose of cultivating CCTS. The pre test and post test results of the groups were analysed using the Analysis of Variance (ANOVA) and the Analysis of Covariance (ANCOVA). The results obtained in the post test and its difference with the pre test results as well as the vast difference between the results obtained by the control group and experimental group showed that the method suggested which is an integrated approach to the teaching of literary texts cultivates critical and creative thinking skills far more effectively than the other methods used by the teachers currently. Findings from both the urban and rural schools were consistent. The findings from this study could contribute to the improvement of pedagogical practices in the teaching and learning of literary texts. The approach can be used as a modal system by the Ministry of Education as it can aid teachers, teacher trainers and syllabus designers to develop a framework appropriate for cultivating CCTS through the teaching of literary texts. This approach can be adopted both at schools as well as at tertiary levels. This approach will not only enhance CCTS among students, it will also cultivate an interest in reading literary texts and other reading materials. In the long run, if this approach is adopted, the objectives of our national leaders to cultivate citizens who have both the ability to think critically and creatively will be achieved.